Thyroid disorders in female subfertility - Rahman, Dilruba; Fatima, Parveen; Banu, Jesmine (Journal of Chittagong Medical College Teachers’ Association, 2009)
Key words: thyroid dysfunction; female subfertility doi: 10.3329/jcmcta.v19i2.3871 Journal of Chittagong Medical College Teachers' Association 2008: 19(2):46-50